2022
DOI: 10.1590/s1678-3921.pab2022.v57.02979
|View full text |Cite
|
Sign up to set email alerts
|

Plot size and number of replicates for experiments with forage sorghum

Abstract: The objective of this work was to define the optimal plot size and number of replicates for the evaluation of the fresh weight of sorghum (Sorghum bicolor) hybrids. Thirty-two uniformity trials were carried out with two hybrids, in two sowing dates and four evaluation periods. Each trial was divided into 48 basic experimental units (BEUs) of 0.5 m2, and fresh weight was determined for each BEU. The mean, variance, coefficient of variation, first-order spatial autocorrelation coefficient, optimal plot size, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The main methods used include the maximum curvature method and the Hatheway method, which are both based on the relationship between the coefficient of variation and the area of the plot. The difference with this study is that the analysis of the coefficient of variation here considers soil moisture, not soil fertility or grain yield [19][20][21][22]. In relation to this, Su Jiakai has described in detail the determination of the area of experimental plots' forage grass in several papers published in Acta Agrestia Sinica; they concluded that the small experimental plots used in many articles led to underrepresentative results, but the methods of determining plot area are limited to information in college textbooks, industry standards, and various industry texts [23], and there is no standard scientific method.…”
Section: Discussionmentioning
confidence: 94%
“…The main methods used include the maximum curvature method and the Hatheway method, which are both based on the relationship between the coefficient of variation and the area of the plot. The difference with this study is that the analysis of the coefficient of variation here considers soil moisture, not soil fertility or grain yield [19][20][21][22]. In relation to this, Su Jiakai has described in detail the determination of the area of experimental plots' forage grass in several papers published in Acta Agrestia Sinica; they concluded that the small experimental plots used in many articles led to underrepresentative results, but the methods of determining plot area are limited to information in college textbooks, industry standards, and various industry texts [23], and there is no standard scientific method.…”
Section: Discussionmentioning
confidence: 94%